Marketing e sua influência no comportamento do consumidor: proposta de reflexão sobre a vulnerabilidade do consumidor permanentemente exposto às práticas comerciais de conquista e manutenção de mercado na sociedade de consumo contemporânea - Mathias, Maria Isabel da Cunha (2010)
The present dissertation proposes a reflection about the permanent exposure of the diffuse collectivity of consumers regarding marketing techniques commercial practices meant to move and foster consumption and the respective consumers legal protection ensured by the Federal Constitution and the Consumer Defense Code considering the pathologies found in contemporary consumption society. This study was divided into five chapters, and its development initially borders citizenship and human dignity as the fundamentals of the Democratic State of Defense, emphasizing consumer protection as a fundamental right enforceable by the State in demanding protection against the violation of rights which occur as a result of relationships between private parties and identifying the constitutional norms that ensure it. The second chapter contemplates the recognition of legitimate interests evidenced in the 20th century, the evolution of the diffuse and collective interest concept and the important accomplishment that represented the Consumer Defense Code in the guardianship of these rights. The third chapter is dedicated to the commercial practices present in the consumer society and deals with marketing as a product and service placement technique in the consumer market, touching on the concept of consumer by comparison, the promotions, the information and mass communication, as well as the vulnerability of the consumer regarding these commercial practices. The fourth chapter presents an overview of the marketing techniques applied in order to influence the behavior of the consumer, through the exposure of concepts, definitions, scopes and methods found in the literature of this area of knowledge followed by the fifth chapter which presents examples which illustrate the behaviors and habits acquired and stimulated by the marketing campaigns. Finally, we can conclude that in compliance with its social pacification function, the consumer rights provides legal protection to the consumer collectivity, taking on a lead role in the resolution of conflicts which occur as a result of the pathologies found in the contemporary consumption market through the application of norms from the Consumer Defense Code, although the Brazilian society is still lacking in public policies and specific regulation in the marketing segment